Formulation And Evaluation Of Sustained Release Matrix Tablets Containing Metformin Hcl And Syzygium cumini - Aruna, N (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The purpose of the research work is to formulate and evaluate Metformin HCl sustained release matrix tablet using Syzygium cumini as a release rate retarding agent which is also antidiabetic in nature by means of wet granulation method. The influence of the release rate by different diluents was studied. Further the optimization of release rate of the drug was carried out by using various polymers such as HPMC K100M, Eudragit RLPO, Carbopol940, Ethyl cellulose. Tablets thus formulated were evaluated for various physical tests like weight variation, hardness, friability and results complied with in the limits. The drug release from all the formulations followed zero order kinetics and Korsmeyer-Peppas mechanism with n value > 0.5 indicating the drug released by non fickian diffusion mechanism. Formulation F6 containing HPMC K 100 M and Ethylcellulose showed the sustained drug release pattern upto 12 hrs which matched the drug release pattern of innovator. The antidiabetic activity of a formulation was evaluated with alloxan model of experimental rats. The results suggested that the syzygium cumini extract acted as a good release rate retarding agent and also showed promising additive antidiabetic activity with Metformin HCl.